ANALYSIS OF TEACHER ERRORS IN APPLYING THE PROBLEM-BASED LEANING MODEL IN THE TEACHER PROFESSIONAL EDUCATION PROGRAM-IN-SERVICE PROGRAM - Yuliawati, Fitri; Aminah Pangestu, Siwi (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2022)
One element that contributes to realizing the process of developing the quality and potential of students is the curriculum. To teach students with 21st-century skills, namely critical thinking, creativity, innovation, collaboration, and mastering technology literacy, teachers competent in dealing with the demands of the 21st century are needed. One learning model that can improve critical thinking skills is the Problem-Based Learning model (PBL). (1) Background: This research analyzes teachers' mistakes in implementing problem-based learning models in the class; (2) Methods: This research method is qualitative and descriptive by collecting data through observation, interviews, and documentation.; (3) Results: The results of this research indicate that the teacher's mistake in applying PBL to learning planning is because the teacher has not understood and mastered the syntax of the problem-based learning (PBL) model; (4) Implications: the research showed a mismatch in the application of the syntax problem-based learning model with the lesson plan.